2019
DOI: 10.3390/ph12030133
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Childhood Maltreatment on Intravenous Ketamine Outcomes for Adult Patients with Treatment-Resistant Depression

Abstract: Childhood maltreatment is associated with a poor treatment response to conventional antidepressants and increased risk for treatment-resistant depression (TRD). The N-methyl-D-aspartate receptor (NDMAR) antagonist ketamine has been shown to rapidly improve symptoms of depression in patients with TRD. It is unknown if childhood maltreatment could influence ketamine’s treatment response. We examined the relationship between childhood maltreatment using the Childhood Trauma Questionnaire (CTQ) and treatment respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…Nemeroff et al [22] reported that adults with chronic depression and early life stress had a more beneficial response to Cognitive Behavioral Analysis System of Psychotherapy (CBASP) than nefazadone and they appeared to have had a more favorable response to CBASP than chronically depressed individuals without early life stress. Likewise, O'Brien et al [33] recently reported that participants with refractory depression and CM had a substantially better response to intravenous ketamine than refractory depressed individuals without CM. More data like these are desperately needed to guide treatment and an improved classification system will facilitate and empower this essential research.…”
Section: Therapeutic Responsementioning
confidence: 97%
“…Nemeroff et al [22] reported that adults with chronic depression and early life stress had a more beneficial response to Cognitive Behavioral Analysis System of Psychotherapy (CBASP) than nefazadone and they appeared to have had a more favorable response to CBASP than chronically depressed individuals without early life stress. Likewise, O'Brien et al [33] recently reported that participants with refractory depression and CM had a substantially better response to intravenous ketamine than refractory depressed individuals without CM. More data like these are desperately needed to guide treatment and an improved classification system will facilitate and empower this essential research.…”
Section: Therapeutic Responsementioning
confidence: 97%
“…Drugs acting on monoamine neurotransmission have dominated the treatment of depression for decades; however, a significant percentage of depressive patients show resistance to pharmacotherapy [17]. Recently, ketamine and its enantiomer S-ketamine have been rediscovered as rapid acting antidepressants with demonstrated efficiency in treatment-resistant depression [18,19]. CBD has also been reported to produce antidepressant-like effects after a single dose [15,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…7 However, the psychotic manifestations, such as perceptual abnormalities, disordered thought and dissociation after ketamine administration are transient and seem to be well tolerated, even in patients with psychotic vulnerability. [8][9][10] Of note, ketamine is also suggested to be more effective in patients with a higher childhood trauma burden, 11 which is a known risk factor for the development of TRD and suicide. 12 Repeated oral S-ketamine was safely combined with other psychiatric drugs and even with the Case report experimental neuromodulation treatment of DBS.…”
Section: Discussionmentioning
confidence: 99%